Compound

JP7608491B2Active Publication Date: 2025-01-06RESONAC CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023020143
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-02-13
Publication Date
2025-01-06
Estimated Expiration
2039-04-26

AI Technical Summary

Benefits of technology

【0021】 本発明よれば、流動性に優れたコンパウンド、コンパウンドを含む成形体、コンパウンドの硬化物、及びコンパウンドの製造方法が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608491000001
    Figure 0007608491000001
Patent Text Reader

Abstract

To provide a compound with excellent fluidity. [Solution] The compound comprises a metal filler containing a first metal powder and a resin composition, wherein the first metal powder contains a plurality of first metal particles, at least a portion of the surface of the first metal particles is covered with glass containing Si, the median diameter of the first metal powder is 1.0 μm or more and 5.0 μm or less, and is processed by transfer molding.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a compound, a molded product, a cured product of the compound, and a method for producing the compound. [Background technology]

[0002] Compounds containing metal powder and a resin composition are used as raw materials for various industrial products depending on the physical properties of the metal powder. For example, compounds are used as raw materials for inductors, sealing materials, electromagnetic shields (EMI shields), bonded magnets, etc. (See Patent Document 1 below.) [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2014-13803 A Summary of the Invention [Problem to be solved by the invention]

[0004] When manufacturing industrial products from compounds, the compounds are supplied and filled into a mold, and parts such as coils are embedded in the compounds. These processes require the compounds to have good fluidity. However, conventional compounds do not have sufficient fluidity. As the particle size of the metal powder decreases, the fluidity of the compounds tends to decrease.

[0005] An object of the present invention is to provide a compound having excellent flowability, a molded article containing the compound, a cured product of the compound, and a method for producing the compound. [Means for solving the problem]

[0006] A compound according to one aspect of the present invention comprises a metal filler containing a first metal powder and a resin composition, wherein the first metal powder contains a plurality of first metal particles, at least a portion of the surface of the first metal particles is covered with glass containing Si, and the median diameter of the first metal powder is 1.0 μm or more and 5.0 μm or less.

[0007] The first metal powder may be an alloy containing Fe.

[0008] The first metal particles may be spherical.

[0009] The resin composition may include a thermosetting resin.

[0010] The compound according to one aspect of the present invention may be a powder or a paste.

[0011] The content of the metal filler in the compound may be 90% by mass or more and less than 100% by mass.

[0012] The metal filler may further include a second metal powder, and the median diameter of the second metal powder may be larger than the median diameter of the first metal powder.

[0013] The median diameter of the second metal powder may be 20.0 μm or more and 30.0 μm or less, the mass of the first metal powder may be M1, the mass of the second metal powder may be M2, 100 × M1 / (M1 + M2) may be 5 or more and 30 or less, and 100 × M2 / (M1 + M2) may be 70 or more and 95 or less.

[0014] The second metal powder may be an alloy containing Fe.

[0015] The second metal particles contained in the second metal powder may be spherical.

[0016] The second metal powder may have a D90 of 40 μm or more and 65 μm or less.

[0017] A molded article according to one aspect of the present invention contains the above-mentioned compound.

[0018] A cured product of a compound according to one aspect of the present invention is a cured product of the above-mentioned compound.

[0019] A method for producing a compound according to one aspect of the present invention is a method for producing the above-mentioned compound, and includes the steps of obtaining a first mixture by mixing a metal filler and a coupling agent, obtaining a second mixture by kneading a resin composition excluding the coupling agent with the first mixture while heating, obtaining a solid by cooling the second mixture, and pulverizing the solid.

[0020] A method for producing a compound according to another aspect of the present invention is a method for producing the above-mentioned compound, comprising the steps of: obtaining a metal filler by mixing a first metal powder and a second metal powder; obtaining a first mixture by mixing the metal filler and a coupling agent; obtaining a second mixture by heating and kneading a resin composition excluding the coupling agent with the first mixture; obtaining a solid by cooling the second mixture; and pulverizing the solid. Effect of the Invention

[0021] According to the present invention, there are provided a compound having excellent flowability, a molded article containing the compound, a cured product of the compound, and a method for producing the compound. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] In the following, preferred embodiments of the present invention will be described, but the present invention is not limited to the following embodiments.

[0023] The compound according to the present embodiment includes a metal filler containing a first metal powder and a resin composition. The metal filler may be rephrased as the entire metal powder contained in the compound. The first metal powder includes a plurality of first metal particles. In other words, the first metal powder means the entirety of a plurality of first metal particles. At least a part of the surface of the first metal particle is covered with glass containing Si (silicon). For example, at least a part of the surface of the first metal particle may be covered with a glass film or glass layer. The glass film or glass layer may be composed of a large number of glass particles containing Si. The compound may further include at least one other metal powder in addition to the first metal powder. The resin composition may cover the surface of each metal particle constituting the metal filler. The resin composition may be present between the metal fillers, and the metal fillers may be bonded to each other via the resin composition. The compound may further include a non-metal filler (e.g., silica or metal oxide).

[0024] As the particle size of each metal particle constituting the metal filler decreases, the gap between the metal particles decreases. As the gap between the metal particles decreases, the filling rate (content) of the metal filler in the compound increases. As the filling rate of the metal filler increases, the relative magnetic permeability of the compound increases. On the other hand, as the particle size of the metal particles decreases, the specific surface area of ​​each metal particle increases. As the specific surface area of ​​the metal particles increases, the metal filler is more likely to aggregate, and the fluidity of the compound is impaired. If the first metal particles are not covered with glass, the first metal powder, which has a relatively small median diameter, is particularly likely to aggregate, and the fluidity of the compound is easily impaired by the aggregation of the first metal powder. However, by covering the surface of the first metal particles with glass, the aggregation of the first metal powder is suppressed, and the frictional force acting between the first metal particles is reduced. As a result, the decrease in the fluidity of the compound caused by the small median diameter of the first metal powder is suppressed. In other words, by covering the surfaces of the first metal particles with glass, it is possible to suppress a decrease in the fluidity of the compound that accompanies an increase in the filling rate of the metal filler.

[0025] The higher the coverage of the glass on the surface of the first metal particles, the less likely the first metal powder is to aggregate, the more likely the frictional force acting between the first metal particles is to be reduced, and the more likely the fluidity of the compound is to be improved. Therefore, the entire surface of the first metal particles may be covered with glass containing Si. However, only a part of the surface of the first metal particles may be covered with glass containing Si. Since the first metal powder is less likely to aggregate and the fluidity of the compound is more likely to be improved, the surfaces of all the first metal particles contained in the first metal powder may be covered with glass containing Si. However, only a part of the surfaces of the first metal particles contained in the first metal powder may be covered with glass containing Si.

[0026] The metal filler may contain at least one other metal powder different from the first metal powder in terms of median diameter in addition to the first metal powder. For example, the metal filler may further contain a second metal powder in addition to the first metal powder. The second metal powder contains a plurality of second metal particles. That is, the second metal powder means the entirety of a plurality of second metal particles. The median diameter of the second metal powder is larger than the median diameter of the first metal powder. If the compound contains only the second metal powder as the metal filler, gaps are likely to be formed between the second metal particles, and the filling rate of the metal filler in the compound is likely to decrease. On the other hand, if the compound contains the first metal powder and the second metal powder as the metal filler, the first metal particles smaller than the second metal particles are likely to be filled in the gaps formed between the second metal particles. As a result, the filling rate of the metal filler in the compound is likely to increase. The relative magnetic permeability of the compound is easily controlled based on the mass ratio of the first metal powder and the second metal powder, and the relative magnetic permeability of the compound is easily increased.

[0027] The surface of the second metal particle may not be covered with the glass containing Si. At least a part of the surface of the second metal particle may be covered with the glass containing Si. By covering the surface of the second metal particle with glass, the aggregation of the second metal powder is suppressed, and the decrease in the flowability of the compound is suppressed. The entire surface of the second metal particle may be covered with the glass containing Si. However, only a part of the surface of the second metal particle may be covered with the glass containing Si. The surfaces of all the second metal particles contained in the second metal powder may be covered with the glass containing Si. Only the surfaces of some of the second metal particles contained in the second metal powder may be covered with the glass containing Si. All the metal powders contained in the compound may be covered with the glass containing Si.

[0028] The median diameter (D50) of the first metal powder is 1.0 μm or more and 5.0 μm or less, preferably 1.5 μm or more and 3.0 μm or less, more preferably 2.17 μm or more and 2.31 μm or less. Since the fine first metal powder having the above D50 is contained in the compound, the filling rate of the metal filler in the compound is likely to be increased. If the D50 of the first metal powder is within the above range and the surface of the first metal particle is not covered with a glass film, the first metal powder is likely to aggregate and the fluidity of the compound is likely to decrease. However, by covering the surface of the first metal particle with glass, even if the D50 of the first metal powder is within the above range, the aggregation of the first metal powder is suppressed and the decrease in the fluidity of the compound is suppressed. The D10 of the first metal powder may be, for example, 1.08 μm or more and 1.2 μm or less. The D90 of the first metal powder may be, for example, 3.88 μm or more and 4.43 μm or less. When the D10 or D90 of the first metal powder is within the above range, the filling rate of the metal filler in the compound is likely to be high. The D10, D50, and D90 of the first metal powder may be calculated from the particle size distribution of the first metal powder based on the volume of the first metal powder. The particle size distribution of the first metal powder may be measured, for example, using a laser diffraction scattering type particle size distribution measuring device. The particle size distribution of the first metal powder may be measured before the first metal powder is mixed with other components of the compound. Each of the D10, D50, and D90 of the first metal powder is a value including the thickness of the glass. The thickness of the glass may be significantly smaller than the particle size of each first metal particle. For example, the scale of the thickness of the glass covering the first metal particles may be nanometers (nm).

[0029] The median diameter (D50) of the second metal powder may be 20.0 μm or more and 30.0 μm or less, preferably 22 μm or more and 28 μm or less, more preferably 24.0 μm or more and 26.0 μm or less. When the fine second metal powder having the above D50 is contained in the compound, the filling rate of the metal filler in the compound is likely to be increased. The D10 of the second metal powder may be, for example, 6.0 μm or more and 12.0 μm or less. The D90 of the second metal powder may be, for example, 40 μm or more and 65 μm or less, preferably 45 μm or more and 65 μm or less. When the D10 or D90 of the second metal powder is within the above range, the filling rate of the metal filler in the compound is likely to be increased. The D10, D50 and D90 of the second metal powder may be calculated from the particle size distribution of the second metal powder based on the volume of the second metal powder. The particle size distribution of the second metal powder may be measured, for example, using a laser diffraction scattering type particle size distribution measuring device. The particle size distribution of the second metal powder may be measured before the second metal powder is mixed with other components of the compound. When the second metal powder is covered with glass, the D10, D50, and D90 of the second metal powder each include the thickness of the glass. The thickness of the glass may be significantly smaller than the particle size of the individual second metal particles. For example, the scale of the thickness of the glass covering the second metal powder may be nanometers (nm).

[0030] The mass of the first metal powder may be represented as M1. The mass of the second metal powder may be represented as M2. When the D50 of the first metal powder is 1.0 μm or more and 5.0 μm or less (preferably 2.17 μm or more and 2.31 μm or less) and the D50 of the second metal powder is 20.0 μm or more and 30.0 μm or less (preferably 24.0 μm or more and 26.0 μm or less), 100×M1 / (M1+M2) may be 5 or more and 30 or less, and 100×M2 / (M1+M2) may be 70 or more and 95 or less. When 100×M1 / (M1+M2) and 100×M2 / (M1+M2) are within the above ranges, the first metal particles are easily filled into the gaps formed between the second metal particles, and the filling rate of the metal filler in the compound is easily increased. As a result, the relative permeability of the compound is easily increased. For the same reasons as above, 100×M1 / (M1+M2) may preferably be 13 or more and 23 or less, and 100×M2 / (M1+M2) may preferably be 77 or more and 87 or less.

[0031] The glass covering the surface of the first metal particle contains at least Si. The glass containing Si may further contain at least one element selected from the group consisting of O (oxygen), B (boron), Na (sodium) and Al (aluminum). The glass may contain, for example, SiO2 (silicate glass) or borosilicate glass. A large number of particles made of glass containing Si may cover the surface of the first metal particle. The means for covering the surface of the first metal particle with the above glass may be, for example, a spray dryer. That is, a surface treatment liquid containing Si may be sprayed onto the first metal powder. The surface treatment liquid containing Si may be a liquid containing glass itself or a liquid containing a raw material of glass. The means for covering the surface of the first metal particle with the above glass may be an impregnation method. For example, the first metal powder may be immersed in a surface treatment liquid containing Si. The first metal powder to which the surface treatment liquid is attached may be heated as necessary.

[0032] The surface of the metal particles constituting the metal filler may be covered with a coupling agent. The surface of the first metal particles may be further covered with a coupling agent. However, the coupling agent covering the metal filler does not correspond to glass containing Si. The first metal particles may have not only a surface covered with glass but also a surface covered with a coupling agent. As the coupling agent, a silane coupling agent is preferable. The compound may further include a metal powder having a surface covered with a coupling agent as a metal powder other than the first metal powder. The compound may further include a metal powder having a surface treated with phosphoric acid (e.g., organic phosphoric acid). For example, the compound may further include a metal powder having a surface covered with phosphate. The first metal particles may further include a surface treated with phosphoric acid as well as a surface covered with glass.

[0033] The first metal powder may contain, for example, at least one selected from the group consisting of a metal element and an alloy. The alloy may contain at least one selected from the group consisting of a solid solution, a eutectic, and an intermetallic compound. The first metal powder may contain one metal element or multiple metal elements. The metal element contained in the first metal powder may be, for example, a base metal element, a noble metal element, a transition metal element, or a rare earth element.

[0034] The metal element contained in the first metal powder may be at least one selected from the group consisting of, for example, iron (Fe), copper (Cu), titanium (Ti), manganese (Mn), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), tin (Sn), chromium (Cr), barium (Ba), strontium (Sr), lead (Pb), silver (Ag), praseodymium (Pr), neodymium (Nd), samarium (Sm) and dysprosium (Dy). The first metal powder may contain elements other than the metal element. The first metal powder may contain, for example, oxygen (O), beryllium (Be), phosphorus (P), boron (B), or silicon (Si). The first metal powder may be a soft magnetic material or a ferromagnetic material.

[0035] The first metal powder may be an alloy containing Fe. The second metal powder may also be an alloy containing Fe. All the metal fillers contained in the compound may be alloys containing Fe. The compound may have a high relative permeability by having an alloy containing Fe as a metal filler. The compound having a high relative permeability may be applied to, for example, an inductor or an EMI filter. The first metal powder may be an alloy containing Fe, Cr, and Si. When the first metal powder is an alloy containing Fe, Cr, and Si, rust of the first metal powder is easily suppressed. In addition, when the first metal powder is an alloy containing Fe, Cr, and Si, core loss in a hardened product of the compound (for example, a part of an inductor other than the coil) is easily suppressed. For the same reason, the second metal powder may also be an alloy containing Fe, Cr, and Si. For the same reason, all the metal fillers contained in the compound may be alloys containing Fe, Cr, and Si.

[0036] The composition of the alloy containing Fe is not limited to the above composition. For example, the first metal powder may contain Fe (iron), Co (cobalt), Ni (nickel), Si (silicon), B (boron), P (phosphorus), C (carbon), element α and element β containing metallic glass, the element α may be at least one element selected from the group consisting of Nb (niobium) and Mo (molybdenum), and the element β may be at least one element selected from the group consisting of Cr (chromium) and Zr (zirconium). The first metal powder may contain at least one selected from the group consisting of Fe-Si alloy, Fe-Si-Al alloy (Sendust), Fe-Ni alloy (Permalloy), Fe-Cu-Ni alloy (Permalloy), and Fe-Co alloy (Permendur).

[0037] The first metal powder may be simple Fe. The first metal powder may include, for example, at least one of an amorphous iron powder and a carbonyl iron powder.

[0038] The first metal powder may include at least one metal magnet selected from the group consisting of Nd-Fe-B based alloys (rare earth magnets), Sm-Co based alloys (rare earth magnets), Sm-Fe-N based alloys (rare earth magnets), and Al-Ni-Co based alloys (alnico magnets).

[0039] The second metal powder may include at least one selected from the group consisting of the above-mentioned metal elements and compounds. The composition of the second metal powder may be the same as that of the first metal powder. The composition of the second metal powder may be different from that of the first metal powder. The metal filler may include at least one other metal powder having a composition different from that of the first metal powder and the second metal powder. The other metal powder may include at least one selected from the group consisting of the above-mentioned metal elements and compounds.

[0040] The first metal powder may include at least one of nanocrystals and amorphous metal. That is, the first metal particles constituting the first metal powder may include at least one of nanocrystals and amorphous metal. The amorphous metal may be a metallic glass. At least a portion of the first metal particles may be single crystal. At least a portion of the first metal particles may be polycrystalline. At least a portion of the first metal particles may be an amorphous metal. When the first metal particles are an amorphous metal, core loss in a device (e.g., an inductor) made from the compound is likely to be reduced.

[0041] The second metal powder may include at least one of nanocrystals and amorphous metal. That is, the second metal particles constituting the second metal powder may include at least one of nanocrystals and amorphous metal. The amorphous metal may be a metallic glass. At least a portion of the second metal particles may be single crystal. At least a portion of the second metal particles may be polycrystalline. At least a portion of the second metal particles may be an amorphous metal. When the second metal particles are an amorphous metal, core loss in a device (e.g., an inductor) made from the compound is likely to be reduced.

[0042] At least some of the first metal particles may be substantially spherical. All of the first metal particles may be substantially spherical. When the first metal particles are substantially spherical, the surfaces of the first metal particles are smooth. As a result, the frictional force acting between the metal fillers is likely to be reduced, and the fluidity of the compound is likely to be improved. For the same reason, at least some of the second metal particles may be substantially spherical. All of the second metal particles may be substantially spherical. For the same reason, all of the metal fillers contained in the compound may be substantially spherical. It is possible to determine whether the first metal particles are spherical or not based on the sphericity of the metal filler. The sphericity of the metal filler can be measured by a particle shape image analyzer. As the particle shape image analyzer, for example, PITA-04 manufactured by Seishin Enterprise Co., Ltd. may be used. The sphericity of the metal filler is measured in a state in which the metal filler is dispersed in purified water. The metal filler is dispersed in purified water by generating ultrasonic waves in water for a predetermined time (for example, 60 seconds). In calculating the sphericity of the metal filler, the influence of agglomerates (secondary particles) of the metal filler may be eliminated by using a certain index. Note that the shapes of the first metal particles and the second metal particles are not limited to spheres.

[0043] The content of the metal filler in the compound may be 90% by mass or more and less than 100% by mass, 93% by mass or more and 99.5% by mass or less, or 94% by mass or more and 99.5% by mass or less. As the content of the metal filler increases, the relative magnetic permeability of the compound tends to increase. On the other hand, as the content of the metal filler increases, the fluidity of the compound tends to decrease. However, even when the content of the metal filler is high, the compound can achieve both high relative magnetic permeability and high fluidity by including the first metal powder. The content of the metal filler in the compound may be rephrased as the filling rate of the metal filler in the compound. The filling rate of the metal filler in the compound may be rephrased as the space factor of the metal filler in the compound. The content of the resin composition in the compound may be greater than 0% by mass and less than 10% by mass, greater than 0.5% by mass and less than 7% by mass, or greater than 0.5% by mass and less than 6% by mass, relative to the mass of the entire compound.

[0044] The resin composition may be a component that may include a resin, a curing agent, a curing accelerator, and an additive. The resin composition may be the remaining components (non-volatile components) excluding the organic solvent and the metal filler. The additive may be the remaining components of the resin composition excluding the resin, the curing agent, and the curing accelerator. The additive is, for example, a coupling agent or a flame retardant. The resin composition may contain wax as an additive. A mixture of the above-mentioned metal filler and the uncured resin composition corresponds to a compound. The compound may be a powder. The compound may be a tablet. The compound may be a paste. A molded body containing the compound is formed by molding the compound. A cured product of the compound is obtained by curing the resin composition in the molded body. The resin compositions described below may be regarded as uncured resin compositions contained in the compound.

[0045] The resin composition functions as a binder for the metal filler and imparts mechanical strength to the molded body and cured body formed from the compound. For example, when the compound is molded under high pressure using a mold, the resin composition fills between the metal filler particles and binds the metal filler particles together. By curing the resin composition in the molded body formed from the compound, the cured resin composition firmly binds the metal filler particles together.

[0046] The resin composition may contain a thermosetting resin. The thermosetting resin may be, for example, at least one selected from the group consisting of an epoxy resin, a phenolic resin, and a polyamideimide resin. When the resin composition contains both an epoxy resin and a phenolic resin, the phenolic resin may function as a curing agent for the epoxy resin. The resin composition may contain a thermoplastic resin. The thermoplastic resin may be, for example, at least one selected from the group consisting of an acrylic resin, polyethylene, polypropylene, polystyrene, polyvinyl chloride, and polyethylene terephthalate. The resin composition may contain both a thermosetting resin and a thermoplastic resin. The resin composition may contain a silicone resin.

[0047] The epoxy resin may be, for example, a resin having two or more epoxy groups in one molecule. The epoxy resin may be, for example, a biphenyl type epoxy resin, a stilbene type epoxy resin, a diphenylmethane type epoxy resin, a sulfur atom-containing type epoxy resin, a novolac type epoxy resin, a dicyclopentadiene type epoxy resin, a salicylaldehyde type epoxy resin, a naphthol-phenol copolymer type epoxy resin, an epoxidized product of an aralkyl type phenol resin, a bisphenol type epoxy resin, a glycidyl ether type epoxy resin of an alcohol, a glycidyl ether type epoxy resin of a paraxylylene and / or metaxylylene-modified phenol resin, or a glycidyl ether type epoxy resin of a terpene-modified phenol resin. resins, cyclopentadiene type epoxy resins, glycidyl ether type epoxy resins of polycyclic aromatic ring modified phenolic resins, glycidyl ether type epoxy resins of naphthalene ring-containing phenolic resins, glycidyl ester type epoxy resins, glycidyl or methylglycidyl type epoxy resins, alicyclic type epoxy resins, halogenated phenol novolac type epoxy resins, ortho-cresol novolac type epoxy resins, hydroquinone type epoxy resins, trimethylolpropane type epoxy resins, and linear aliphatic epoxy resins obtained by oxidizing an olefin bond with a peracid such as peracetic acid.

[0048] Among epoxy resins, crystalline epoxy resins are preferred. Although the molecular weight of crystalline epoxy resins is relatively low, crystalline epoxy resins have a relatively high melting point and excellent fluidity. The crystalline epoxy resin (highly crystalline epoxy resin) may be at least one selected from the group consisting of hydroquinone type epoxy resins, bisphenol type epoxy resins, thioether type epoxy resins, and biphenyl type epoxy resins. Commercially available crystalline epoxy resins include, for example, Epicron 860, Epicron 1050, Epicron 1055, Epicron 2050, Epicron 3050, Epicron 4050, Epicron 7050, Epicron HM-091, Epicron HM-101, Epicron N-730A, Epicron N-740, Epicron N-770, Epicron N-775, Epicron N-865, Epicron HP-4032D, Epicron HP-7200L, Epicron HP-7200, Epicron HP-7200H, Epicron HP-7200HH, Epicron HP-7200HHH, Epicron HP-4700, Epicron HP-4710, Epicron HP-4770, Epicron HP-5000, Epicron HP-60 00, and N500P-2 (all product names manufactured by DIC Corporation), NC-3000, NC-3000-L, NC-3000-H, NC-3100, CER-3000-L, NC -2000-L, XD-1000, NC-7000-L, NC-7300-L, EPPN-501H, EPPN-501HY, EPPN-502H, EOCN-1020, EO It may be at least one selected from the group consisting of CN-102S, EOCN-103S, EOCN-104S, CER-1020, EPPN-201, BREN-S, BREN-10S (all of which are trade names manufactured by Nippon Kayaku Co., Ltd.), YX-4000, YX-4000H, YL4121H, and YX-8800 (all of which are trade names manufactured by Mitsubishi Chemical Corporation).

[0049] The resin composition may contain one type of epoxy resin among the above-mentioned epoxy resins. The resin composition may contain two or more types of epoxy resins among the above-mentioned epoxy resins.

[0050] Curing agents are classified into those that cure resins at temperatures ranging from low to room temperature, and heat-curing curing agents that cure resins by heating. Examples of curing agents that cure resins at temperatures ranging from low to room temperature include aliphatic polyamines, polyaminoamides, and polymercaptans. Examples of heat-curing curing agents include aromatic polyamines, acid anhydrides, phenolic resins, phenolic novolac resins, and dicyandiamide (DICY).

[0051] The phenolic resin may be at least one selected from the group consisting of, for example, aralkyl type phenolic resin, dicyclopentadiene type phenolic resin, salicylaldehyde type phenolic resin, novolac type phenolic resin, copolymer type phenolic resin of benzaldehyde type phenol and aralkyl type phenol, paraxylylene and / or metaxylylene modified phenolic resin, melamine modified phenolic resin, terpene modified phenolic resin, dicyclopentadiene type naphthol resin, cyclopentadiene modified phenolic resin, polycyclic aromatic ring modified phenolic resin, biphenyl type phenolic resin, and triphenylmethane type phenolic resin. The phenolic resin may be a copolymer composed of two or more of the above. As a commercially available product of the phenolic resin, for example, Tamanoru 758 manufactured by Arakawa Chemical Industries Co., Ltd., or HP-850N manufactured by Hitachi Chemical Co., Ltd. may be used.

[0052] The phenol novolac resin may be, for example, a resin obtained by condensing or co-condensing phenols and / or naphthols with aldehydes under an acid catalyst. The phenols constituting the phenol novolac resin may be, for example, at least one selected from the group consisting of phenol, cresol, xylenol, resorcin, catechol, bisphenol A, bisphenol F, phenylphenol, and aminophenol. The naphthols constituting the phenol novolac resin may be, for example, at least one selected from the group consisting of α-naphthol, β-naphthol, and dihydroxynaphthalene. The aldehydes constituting the phenol novolac resin may be, for example, at least one selected from the group consisting of formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, and salicylaldehyde.

[0053] The curing agent may be, for example, a compound having two phenolic hydroxyl groups in one molecule. The compound having two phenolic hydroxyl groups in one molecule may be, for example, at least one selected from the group consisting of resorcin, catechol, bisphenol A, bisphenol F, and substituted or unsubstituted biphenol.

[0054] The resin composition may contain one of the above phenolic resins. The resin composition may include a plurality of the above phenolic resins. The resin composition may contain one of the above curing agents. The resin composition may contain a plurality of the above curing agents. As a commercially available phenolic resin, for example, Tamanol 758 manufactured by Arakawa Chemical Industries Co., Ltd., or HP-850N manufactured by Hitachi Chemical Co., Ltd. may be used.

[0055] The ratio of the active group (phenolic OH group) in the curing agent that reacts with the epoxy group in the epoxy resin may be preferably 0.5 to 1.5 equivalents, more preferably 0.9 to 1.4 equivalents, and even more preferably 1.0 to 1.2 equivalents relative to 1 equivalent of the epoxy group in the epoxy resin. When the ratio of the active group in the curing agent is less than 0.5 equivalents, the amount of OH per unit weight of the cured epoxy resin decreases, and the curing speed of the resin composition (epoxy resin) decreases. When the ratio of the active group in the curing agent is less than 0.5 equivalents, the glass transition temperature of the obtained cured product decreases, or sufficient elastic modulus of the cured product cannot be obtained. On the other hand, when the ratio of the active group in the curing agent exceeds 1.5 equivalents, the mechanical strength of the sealing material formed from the compound tends to decrease. However, even when the ratio of the active group in the curing agent is outside the above range, the effect of the present invention can be obtained.

[0056] The curing accelerator is not limited as long as it is a composition that reacts with the epoxy resin to promote the curing of the epoxy resin. The curing accelerator may be, for example, an imidazole such as an alkyl group-substituted imidazole or benzimidazole. The resin composition may include one type of curing accelerator. The resin composition may include multiple types of curing accelerators. When the resin composition contains a curing accelerator, the moldability and releasability of the compound are easily improved. When the resin composition contains a curing accelerator, the mechanical strength of the sealing material produced using the compound is improved, and the storage stability of the compound under high temperature and high humidity environments is improved. As a commercially available product of the imidazole-based curing accelerator, for example, at least one selected from the group consisting of 2MZ-H, C11Z, C17Z, 1,2DMZ, 2E4MZ, 2PZ-PW, 2P4MZ, 1B2MZ, 1B2PZ, 2MZ-CN, C11Z-CN, 2E4MZ-CN, 2PZ-CN, C11Z-CNS, 2P4MHZ, TPZ, and SFZ (all trade names of Shikoku Chemical Industry Co., Ltd.) may be used. Among these, imidazole-based curing accelerators having a long-chain alkyl group are preferred, and C11Z-CN (1-cyanoethyl-2-undecylimidazole) is preferred.

[0057] The amount of the curing accelerator is not particularly limited as long as it is an amount that can provide a curing acceleration effect. However, from the viewpoint of improving the curability and fluidity of the resin composition when absorbing moisture, the amount of the curing accelerator may be preferably 0.1 to 30 parts by mass, more preferably 1 to 15 parts by mass, relative to 100 parts by mass of the epoxy resin. The content of the curing accelerator is preferably 0.001 parts by mass or more and 5 parts by mass or less relative to the total mass of the epoxy resin and the curing agent (e.g., phenolic resin). When the amount of the curing accelerator is less than 0.1 parts by mass, it is difficult to obtain a sufficient curing acceleration effect. When the amount of the curing accelerator is more than 30 parts by mass, the storage stability of the compound is likely to decrease. However, even when the amount and content of the curing accelerator are outside the above ranges, the effect of the present invention can be obtained.

[0058] The coupling agent improves the adhesion between the resin composition and the metal filler, and improves the flexibility and mechanical strength of the sealing material formed from the compound. The coupling agent may be, for example, at least one selected from the group consisting of silane-based compounds (silane coupling agents), titanium-based compounds, aluminum compounds (aluminum chelates), and aluminum / zirconium-based compounds. The silane coupling agent may be, for example, at least one selected from the group consisting of epoxy silane, mercapto silane, amino silane, alkyl silane, ureido silane, acid anhydride silane, and vinyl silane. In particular, aminophenyl-based silane coupling agents are preferred. The compound may include one of the above coupling agents, or may include multiple of the above coupling agents.

[0059] For the purpose of improving the environmental safety, recyclability, moldability and low cost of the compound, the compound may contain a flame retardant. The flame retardant may be at least one selected from the group consisting of bromine-based flame retardants, bulb flame retardants, hydrated metal compound-based flame retardants, silicone-based flame retardants, nitrogen-containing compounds, hindered amine compounds, organometallic compounds and aromatic engineering plastics. The compound may contain one or more of the above flame retardants.

[0060] The resin composition may contain a wax. The wax increases the fluidity of the compound during molding (e.g., transfer molding) of the compound and also functions as a mold release agent. The wax may be at least one of a fatty acid such as a higher fatty acid and a fatty acid ester.

[0061] Examples of the wax include fatty acids such as montanic acid, stearic acid, 12-hydroxystearic acid, and lauric acid, and esters thereof; fatty acid salts such as zinc stearate, calcium stearate, barium stearate, aluminum stearate, magnesium stearate, calcium laurate, zinc linoleate, calcium ricinoleate, and zinc 2-ethylhexanoate; and fatty acid salts such as stearic acid amide, oleic acid amide, erucic acid amide, behenic acid amide, palmitic acid amide, lauric acid amide, hydroxystearic acid amide, methylene bisstearic acid amide, ethylene bisstearic acid amide, ethylene bislauric acid amide, distearyl adipate amide, ethylene bisoleic acid amide, dioleyl adipate amide, N-stearyl stearic acid amide. fatty acid esters such as butyl stearate; alcohols such as ethylene glycol and stearyl alcohol; polyethers such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol and modified products thereof; polysiloxanes such as silicone oil and silicone grease; fluorine compounds such as fluorine-based oil, fluorine-based grease, fluorine-containing resin powder, and waxes such as paraffin wax, polyethylene wax, amide wax, polypropylene wax, ester wax, carnauba wax, microwax, and the like.

[0062] The compound according to the present embodiment has excellent fluidity. Therefore, the compound according to the present embodiment can be easily processed into a desired shape by extrusion molding or transfer molding. The physical properties of the molded body containing the compound or the cured product of the compound can be freely controlled based on the composition of the metal filler or the resin composition. The physical properties are, for example, electromagnetic properties or thermal conductivity. For these reasons, the compound can be used for various industrial products or their raw materials. The industrial products manufactured using the compound may be, for example, automobiles, medical devices, electronic devices, electrical devices, information and communication devices, home appliances, audio devices, and general industrial devices. When the compound contains a soft magnetic material as a metal filler, the compound may be used as a sealant for inductors, a magnetic core for inductors, an EMI shield, or a magnetic core for a transformer. When the compound contains a metal magnet as a metal filler, the compound may be used as a raw material for bonded magnets.

[0063] (Compound manufacturing method) An example of a method for producing the compound according to the present invention will be described below, however, the method for producing the compound according to the present invention is not limited to the following method.

[0064] The method for producing the compound according to this embodiment includes a first mixing step, a second mixing step, a cooling step, and a grinding step.

[0065] In the first mixing step, the metal filler and the coupling agent are mixed to obtain a first mixture. In the first mixing step, the coupling agent is bonded to the surface of each metal particle constituting the metal filler. In other words, a part or the whole of the surface of each metal particle is covered with the coupling agent. As a result, the surface of the metal filler is easily covered with the resin composition via the coupling agent, the metal filler is easily dispersed in the compound, and the filling rate of the metal filler in the compound is easily increased.

[0066] The metal filler mixed with the coupling agent includes at least a first metal powder. The surface of each first metal particle included in the first metal powder is covered with a glass containing Si in advance. Since the filling rate of the metal filler in the compound is likely to increase, the metal filler mixed with the coupling agent preferably includes both a first metal powder and a second metal powder. The surface of each second metal particle included in the second metal powder does not have to be covered with a glass containing Si. The surface of each second metal particle included in the second metal powder may be covered with a glass containing Si in advance. When the metal filler includes both the first metal powder and the second metal powder, the metal filler may be obtained by mixing the first metal powder and the second metal powder before the first mixing step.

[0067] In the second mixing step following the first mixing step, the resin composition excluding the coupling agent and the first mixture are kneaded while being heated to obtain a second mixture. That is, in the second mixing step, the components of the resin composition other than the coupling agent are kneaded with the first mixture. The components of the resin composition other than the coupling agent may be, for example, a thermosetting resin, a curing agent, a curing accelerator, and an additive. The additive may be, for example, at least one of a wax and a flame retardant. Before the second mixing step, the thermosetting resin, the curing agent, the curing accelerator, and the additive may be premixed to obtain a resin mixture. Then, in the second mixing step, the resin mixture and the first mixture are kneaded while being heated to obtain a second mixture. The second mixture may be a paste.

[0068] The temperature of the second mixture in the second mixing step may be adjusted according to the composition of the resin composition. The temperature of the second mixture in the second mixing step may be, for example, 50°C or more and 150°C or less, preferably 60°C or more and 120°C or less, more preferably 80°C or more and 110°C or less. When the temperature of the second mixture is within the above range, the resin composition in the second mixture is likely to soften, the resin composition is likely to cover the surface of the metal particles, and the curing of the resin composition during the second mixing step is likely to be suppressed. When the temperature of the second mixture is too low, the second mixture is not sufficiently kneaded, the moldability of the compound is impaired, and the degree of curing of the compound varies. When the temperature of the second mixture is too high, the curing of the resin composition proceeds during the second mixing step, and the fluidity and moldability of the compound are likely to be impaired. The time for kneading the second mixture in the second mixing step may be adjusted according to the performance of the kneading means (e.g., a biaxial pressure kneader) used in the second mixing step and the volume of the second mixture.

[0069] In the cooling step following the second mixing step, the second mixture is cooled to obtain a solid. The second mixture may be cooled at room temperature.

[0070] In the grinding step following the cooling step, the solid is ground. The powder obtained by grinding the solid may itself be used as the compound. The powder obtained by the grinding step may be classified to remove coarse particles from the powder. The powder obtained by the grinding step may be molded to produce tablets made of the compound.

[0071] Through the above manufacturing method, the compound is completed. EXAMPLES

[0072] The present invention will be described in more detail with reference to the following examples and comparative examples, although the present invention is not limited to the following examples in any way.

[0073] Example 1 [Preparation of compound powder] <Preparation of Metal Filler> The first metal powder and the second metal powder were placed in a bag and the bag was closed. The bag was shook with both hands for 3 minutes to mix the first metal powder and the second metal powder, thereby obtaining a metal filler. The bag was made of PE (polyethylene). The dimensions of the bag were 470 mm x 670 mm.

[0074] The first metal powder was composed of a large number of first metal particles. The median diameter of the first metal powder was 2.17 μm or more and 2.31 μm or less. Each first metal particle was composed of an alloy particle and a large number of glass particles covering the surface of the alloy particle. Each alloy particle contained Fe, Cr, and Si. Each glass particle covering the surface of the alloy particle contained Si. The particle size of each glass particle was significantly smaller than the median diameter of the first metal powder. Each first metal particle was approximately spherical. The mass M1 of the first metal powder was 770.8 g.

[0075] As the second metal powder, a powder of an amorphous alloy containing iron was used. The powder of the amorphous alloy containing iron was KUAMET 9A4-II manufactured by Epson Atmix Corporation. The median diameter of the second metal powder was 25.0 μm. The amorphous alloy particles (second metal particles) constituting the second metal powder were approximately spherical. The mass M2 of the second metal powder was 3511.2 g.

[0076] 100×M1 / (M1+M2) was 18. 100×M2 / (M1+M2) was 82.

[0077] <First mixing process> Methacrylsilane (a silane coupling agent) was added to the metal filler in the bag. The mass of the methacrylsilane was 5.43 g. The methacrylsilane was KBM-503 manufactured by Shin-Etsu Chemical Co., Ltd. The bag was shaken with both hands for 3 minutes to mix the metal filler and methacrylsilane, thereby obtaining a first mixture. The first mixing step covered the surface of each metal particle constituting the metal filler with methacrylsilane.

[0078] <Second mixing process> In the second mixing step, a different bag was used. The size of the bag used in the second mixing step was 205 x 300 mm. This bag was made of PE (polyethylene). The thermosetting resin, hardener, hardening accelerator and wax powder were placed in the bag and the bag was closed. The resin mixture was obtained by mixing the contents of the bag by shaking the bag with both hands for 3 minutes. The mass and composition of each of the thermosetting resin, hardener, hardening accelerator and wax powder are shown below. Both NC3000-H and NC3000 below are epoxy resins. 90.9 g of thermosetting resin (NC3000-H manufactured by Nippon Kayaku Co., Ltd.) 39.0 g of thermosetting resin (NC3000 manufactured by Nippon Kayaku Co., Ltd.) 48.2 g of hardener (phenol novolac resin, HP-850N manufactured by Hitachi Chemical Co., Ltd.) 2.6 g of hardener (imidazole-based epoxy resin hardener, C17Z from Shikoku Kasei Co., Ltd.) 15.7 g wax powder (Licowax E from Clariant Chemicals)

[0079] The above first mixture and resin mixture were placed in the vessel of a twin-axis pressure kneader. The first mixture and resin mixture in the vessel were kneaded under pressure with the kneader to obtain a second mixture. The second mixture was a paste. The temperature in the vessel during kneading was 82°C. The rotation speed of the kneader was 40 rpm. The kneading time was 1 minute. A pressure kneader (PS1-5MHB-H type kneader) manufactured by Nippon Spindle Mfg. Co., Ltd. (formerly Moriyama Mfg. Co., Ltd.) was used as the twin-axis pressure kneader.

[0080] <Cooling process> The second mixture was cooled to room temperature to give a solid.

[0081] <Crushing process> The solid matter was pulverized to obtain a powdered compound. Large particles were removed from the compound by classification using a sieve with a mesh size of 2 mm.

[0082] By the above method, the compound of Example 1 was produced. The content (volume factor) of the metal filler in the compound was 95.5 mass %.

[0083] [Liquidity assessment] The compound of Example 1 was loaded into a transfer tester. The compound's spiral flow amount was measured at a mold temperature of 175°C, injection pressure of 4.1MPa, and molding time of 420 seconds. The spiral flow amount is the length of the compound flowing in the groove formed in the mold. In other words, the spiral flow amount is the flow distance of the softened or liquefied compound. The shape of the groove through which the compound flows is a spiral curve (Archimedes' spiral). The easier the compound flows, the larger the spiral flow amount. In other words, the spiral flow amount of a compound with excellent fluidity is large. As the transfer tester, a 100KN transfer molding machine (PZ-10 type) manufactured by Kodaira Seisakusho Co., Ltd. was used. As the mold, a mold for measuring spiral flow according to ASTM D3123 was used. The spiral flow amount of Example 1 is shown in Table 1 below.

[0084] [Measurement of relative permeability] A toroidal molded body was produced from the compound of Example 1 using a transfer tester and a mold. The mold temperature was 175°C, the injection pressure was 4.1 MPa, and the molding time was 420 seconds. The molded body had an outer diameter of 20 mm, an inner diameter of 12 mm, and a thickness of 2 mm. A 100KN transfer molding machine (PZ-10 type) manufactured by Kodaira Manufacturing Co., Ltd. was used as the transfer tester. A mold capable of obtaining a toroidal shape was used as the mold. The primary winding was wound around the molded body with 5 turns, and the secondary winding was wound around the molded body with 5 turns. The relative permeability μ of the sample produced by the above method was S The relative permeability μ S is shown in Table 1 below. Relative permeability μ S The measurement was performed using a BH analyzer (SY-8258) manufactured by Iwasaki Electric Co., Ltd. The frequency used for measuring the relative permeability was 1 MHz.

[0085] Example 2 By changing the mass ratio of the first mixture and the resin mixture, the content of the metal filler in the compound of Example 2 was adjusted to 95.0 mass%. The compound of Example 2 was produced in the same manner as Example 1 except for the content of the metal filler. The spiral flow amount of the compound of Example 2 was measured in the same manner as Example 1. The spiral flow amount of Example 2 is shown in Table 1 below. The relative magnetic permeability of the compound of Example 2 was measured in the same manner as Example 1. The relative magnetic permeability of Example 2 is shown in Table 1 below.

[0086] Comparative Example 1 As the metal filler of Comparative Example 1, only the second metal powder was used. As in Example 1, the content of the metal filler in the compound of Comparative Example 1 was adjusted to 95.5 mass%. The compound of Comparative Example 1 was produced in the same manner as in Example 1, except for the metal filler. The spiral flow amount of the compound of Comparative Example 1 was measured in the same manner as in Example 1. The spiral flow amount of Comparative Example 1 is shown in Table 1 below. The relative magnetic permeability of the compound of Comparative Example 1 was measured in the same manner as in Example 1. The relative magnetic permeability of Comparative Example 1 is shown in Table 1 below.

[0087] Comparative Example 2 As the metal filler of Comparative Example 2, only the second metal powder was used. As in Example 2, the content of the metal filler in the compound of Comparative Example 2 was adjusted to 95.0 mass%. The compound of Comparative Example 2 was produced in the same manner as in Example 1, except for the metal filler and its content. The spiral flow amount of the compound of Comparative Example 2 was measured in the same manner as in Example 1. The spiral flow amount of Comparative Example 2 is shown in Table 1 below. The relative magnetic permeability of the compound of Comparative Example 2 was measured in the same manner as in Example 1. The relative magnetic permeability of Comparative Example 2 is shown in Table 1 below.

[0088] [Table 1] [Industrial Applicability]

[0089] The compound according to the present invention has excellent fluidity and can be easily molded into various shapes of industrial products.

Claims

1. A compound comprising a metal filler containing a first metal powder and a resin composition, the first metal powder comprises a plurality of first metal particles; at least a portion of a surface of the first metal particle is covered with a glass containing Si, The first metal powder has a median diameter of 1.0 μm or more and 5.0 μm or less, The compound is a powder, tablet, or paste compound; Processed by transfer molding, Compound.

2. The resin composition includes an epoxy resin, The epoxy resin includes an epoxidized product of an aralkyl-type phenolic resin. The compound of claim 1.

3. The resin composition contains a wax, The wax comprises a Montan acid ester. A compound according to claim 1 or 2.

4. The resin composition contains a curing accelerator, The curing accelerator includes an imidazole. A compound according to any one of claims 1 to 3.

5. The first metal powder is an alloy containing Fe. A compound according to any one of claims 1 to 4.

6. the first metal particles are spherical; A compound according to any one of claims 1 to 5.

7. The resin composition includes a thermosetting resin. A compound according to any one of claims 1 to 6.

8. The content of the metal filler is 90% by mass or more and less than 100% by mass. A compound according to any one of claims 1 to 7.

9. the metal filler further comprises a second metal powder; The median diameter of the second metal powder is larger than the median diameter of the first metal powder. A compound according to any one of claims 1 to 8.

10. The second metal powder has a median diameter of 20.0 μm or more and 30.0 μm or less, The mass of the first metal powder is M1; The mass of the second metal powder is M2; 100×M1 / (M1+M2) is 5 or more and 30 or less, 100×M2 / (M1+M2) is equal to or greater than 70 and equal to or less than 95; The compound according to claim 9.

11. The second metal powder is an alloy containing Fe. A compound according to claim 9 or 10.

12. The second metal particles contained in the second metal powder are spherical. A compound according to any one of claims 9 to 11.

13. The D90 of the second metal powder is 40 μm or more and 65 μm or less. A compound according to any one of claims 9 to 12.

14. The second metal powder has a median diameter of 20.0 μm or more and 28 μm or less. A compound according to any one of claims 9 to 13.

15. The metal filler is a soft magnetic material. A compound according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • Powder magnetic core and method of manufacturing the same

    JP2011040473A

  • Powder magnetic core, powder for magnetic core and manufacturing method for the same

    JP2012049203A

  • Resin composition and coil

    JP2013053247A

  • JP2014‐13803A

  • Compound for rare earth bond magnet use, rare earth bond magnet, and method for manufacturing rare earth bond magnet

    JP2015153778A